2015
DOI: 10.3390/ijms161126063
|View full text |Cite
|
Sign up to set email alerts
|

The Deubiquitinase USP17 Regulates the Stability and Nuclear Function of IL-33

Abstract: IL-33 is a new member of the IL-1 family cytokines, which is expressed by different types of immune cells and non-immune cells. IL-33 is constitutively expressed in the nucleus, where it can act as a transcriptional regulator. So far, no direct target for nuclear IL-33 has been identified, and the regulation of IL-33 nuclear function remains largely unclear. Here, we report that the transcription of type 2 inflammatory cytokine IL-13 is positively regulated by nuclear IL-33. IL-33 can directly bind to the cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 30 publications
0
28
0
1
Order By: Relevance
“…TRAF2 and TRAF3 are known to undergo K63-linked self-ubiquitination for protein–protein interactions [ 25 , 26 ], therefore we also examined whether USP17 promotes TRAF2 and TRAF3 deubiquitination, and whether this deubiquitination activity is required for promoting inflammatory responses by USP17. It is known that cysteine residue 89 in the USP domain is required for the deubiquitination activity of USP17 [ 35 37 ], thus this cysteine was mutated into a serine residue (C89S) to generate an inactive mutant. When coexpressed in HEK293 cells, wild-type USP17 promoted K63-linked TRAF2 and TRAF3 deubiquitination, whereas the C89S mutant did not (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TRAF2 and TRAF3 are known to undergo K63-linked self-ubiquitination for protein–protein interactions [ 25 , 26 ], therefore we also examined whether USP17 promotes TRAF2 and TRAF3 deubiquitination, and whether this deubiquitination activity is required for promoting inflammatory responses by USP17. It is known that cysteine residue 89 in the USP domain is required for the deubiquitination activity of USP17 [ 35 37 ], thus this cysteine was mutated into a serine residue (C89S) to generate an inactive mutant. When coexpressed in HEK293 cells, wild-type USP17 promoted K63-linked TRAF2 and TRAF3 deubiquitination, whereas the C89S mutant did not (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We thus proposed that IL-33 may be a dual function protein, acting both extracellularly as an IL-1 family cytokine, and intracellularly as a nuclear factor regulating gene expression 2 . Nuclear functions of IL-33 in transcriptional regulation have been proposed in several recent studies 34 35 36 . However, to date, no large scale study has been performed to demonstrate a global role of endogenous nuclear IL-33 in the regulation of gene or protein expression.…”
mentioning
confidence: 99%
“…Hou et al found that the E3 deubiquitinase USP21 is a positive regulator of GATA3 in asthma ( 23 ). Other studies indicate that the deubiquitinase USP17 regulates the stability and nuclear function of IL-33, and is also a positive regulator of retinoic acid-related orphan nuclear receptor γt (RORγt) in Th17 cells ( 24 , 25 ). In this study, we not only found an interaction between USP4 and IRF4, but also proved the effect of USP4 on the stabilization and deubiquitination of IRF4.…”
Section: Discussionmentioning
confidence: 99%